Long-term outcomes of endoscopic submucosal dissection for early gastric cancer: a retrospective comparison with conventional endoscopic resection in a single center - Tanabe, Satoshi; Ishido, Kenji; Higuchi, Katsuhiko; Sasaki, Tohru; Katada, Chikatoshi; Azuma, Mizutomo; Naruke, Akira; Kim, Myungchul; Koizumi, Wasaburo (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2014)
Background Few studies have compared the outcomes of endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) in patients with early gastric cancer. Methods We studied 780 lesions for which endoscopic treatment was indicated according to the Japanese Gastric Cancer Association (JGCA) criteria or the extended National Cancer Center (NCC) criteria from April 1995 to December 2007. A total of 359 lesions were treated by endoscopic aspiration mucosectomy (EAM) between April 1995 and March 2003 (EAM group), and 421 lesions were treated by ESD between April 2003 and December 2007 (ESD group). Long-term outcomes (local recurrence rate, overall survival) were compared between the groups. Results The median follow-up was 73 months in the EAM group and 65 months in the ESD group. Overall, the local recurrence rate was significantly lower in the ESD group (0.2 %, 1/421) than in the EAM group (4.2 %, 15/359) ( p < 0.05). For lesions meeting the JGCA criteria, the local recurrence rate was 2.9 % in the EAM group and 0 % in the ESD group ( p < 0.05). For lesions meeting the NCC criteria, the local recurrence rate was 12.5 % in the EAM group and 0.6 % in the ESD group ( p < 0.05). There was no significant difference between the groups in overall survival. Conclusions On long-term follow-up, ESD was associated with a lower rate of local recurrence than EAM for lesions that met the JGCA or the NCC criteria. From the point of view of radical curability, ESD can be recommended for the management of lesions that meet either set of criteria.